With Distance in His Eyes : The Environmental Life and Legacy of Stewart Udall - Einberger, Scott (Book collections on Project MUSE., 2018)
"Perhaps no other public official or secretary of the interior has ever had as much success in environmental protection, natural resource conservation, and outdoor recreation opportunity creation as Stewart Udall. A progressive Mormon raised in rural Arizona, Udall served in the presidential cabinets of John F. Kennedy and Lyndon Baines Johnson from 1961-1969. During these eight years, he established dozens of new national park units and national wildlife refuges, wrote the Endangered Species Preservation Act, lobbied for unpolluted water, and offered ways to beautify urban spaces and bring the impoverished out of poverty. Later in life, he offered sound solutions for a society obsessed with oil. In a day and age of partisan politics, poor congressional approval ratings, global warming and climate change, what can we learn from this farsighted individual? In this book - the first environmental biography of Stewart Udall - environmental historian and public lands enthusiast Scott Einberger chronicles the writings, sayings, and doings of a highly important conservationist and environmentalist. Intimate moments including Udall's learning of the Kennedy assassination, his push for civil rights for African Americans, his warnings about global warming 50 years prior to Al Gore's Nobel Prize film, and his meeting in the U.S.S.R. with Nikita Khrushchev - the first Kennedy cabinet member to do so - are also shared"--Provided by publisher.